(untitled) (International Journal of Environmental Sciences, 2025)
This study explores the critical relationship between environmental health quality and regional competitiveness, aiming to clarify how ecological conditions shape economic resilience, innovation, and regional development. A qualitative systematic literature review was conducted, synthesizing 127 peer-reviewed articles from the past 10–15 years, selected based on relevance to regional competitiveness, environmental health, and productivity. Using deductive reasoning and structured data tabulation, the study examined theoretical frameworks, empirical evidence, and policy implications. The findings indicate that improved environmental health such as reduced pollution and enhanced public health outcomes significantly enhances workforce productivity, reduces healthcare burdens, and increases regional attractiveness to investment. Furthermore, the integration of environmental health indicators into competitiveness frameworks enables more holistic regional planning, aligning economic growth with sustainability goals. Evidence from multiple sectors (tourism, manufacturing, agriculture, and health) illustrates that environmental quality influences innovation capacity, labor market dynamics, and regional branding. Governance models emphasizing sustainability, multi-sectoral collaboration, and stakeholder engagement are shown to be essential for successful integration. The study concludes that environmental health should be viewed as a foundational component of regional competitiveness and recommends developing multidimensional indicators, adaptive strategies, and inclusive governance frameworks for future research and policy innovation.